A Case Report of Acute Acalculous Cholecystitis and Acute Hemorrhagic Cystitis due to Salmonella Typhi - Hatice Beyazal Polat; Mehmet Beyazal; Fatma Beyazal Çeliker (Case Reports in Medicine)
Acute acalculous cholecystitis and acute hemorrhagic cystitis due to Salmonella Typhi are a rare condition. A 24-year-old female patient was admitted to our clinic with abdominal pain, nausea, fever, headache, urinary burning, and bloody urine. Based on clinical, laboratory, and radiological evaluations, the patient was diagnosed with acute acalculous cholecystitis and acute hemorrhagic cystitis due to Salmonella Typhi. The patient was treated with intravenous ceftriaxone for two weeks. After the treatment, the patient's clinical and laboratory findings improved. Acute acalculous cholecystitis due to Salmonella Typhi concomitant with acute hemorrhagic cystitis is very rare and might be difficult to diagnose. Infectious agents such as Salmonella Typhi should be considered when acute acalculous cholecystitis and acute hemorrhagic cystitis are detected in adult patients with no underlying diseases.